PERTUMBUHAN DAN PRODUKSI KEDELAI AKIBAT INOKULASI BAKTERI RHIZOBIUM DAN PENAMBAHAN HARA AIR LAUT - Fuskhah, Eny; Darmawati, Adriani (Pastura; Vol 6 No 1 (2016): Pastura Vol. 6 No. 1 Tahun 2016DO - 10.24843/Pastura.2016.v06.i01.p03, 2019)
The research aim is to use sea water as nutrient source of plant especially soybean, so it reduces amount of anorganic fertilizer usage. The research held in green house of Ecology and Plant Production Laboratory of Animal Husbandry and Agriculture Faculty, Diponegoro University Semarang. Sea water as sample was taken from Semarang Marina Beach. Soybean which choosen is local bean of Grobogan. The design arranged was completely randomized design with factorial design 4 x 2 in 4 replications. First factor was sea water salinity level, L0 = without sea water and without mulch, L1 = sea water EC 1 mmhos/cm and water hyacinth mulch of 8 tons/ha, L2 = sea water EC 2 mmhos/cm and water hyacinth mulch of 8 tons/ha, L3 = sea water EC 3 mmhos/cm and water hyacinth mulch of 8 tons/ha. The second factor was Rhizobium inoculation, R1 = without rhizobium inoculation, and R2 = with Rhizobium inoculation. The parameters were length plant, number of leaves, fresh weight production of shoot and dry matter production. Based on variant analysis, showed no influenced between sea water salinity level and rhizobium inoculation againt to length plant, number of leaves, fresh weight production of shoot and dry matter production. Sea water and rhizobium inoculation tended to increase growth and production of soybean. Key words : soybean, nutrient of sea water, rhizobium, growth, production.